1992
DOI: 10.1172/jci115896
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor antagonist in normal and psoriatic epidermis.

Abstract: The objective of these studies was to characterize the IL-1 inhibitory activity present in normal and psoriatic epidermis from clinically stable lesions. Fractionation of normal epidermal cytosol on a molecular sizing column failed to reveal the presence of IL-1 inhibitory bioactivity. However, specific ELISAs indicated that both the IL-1 receptor antagonist (IL-lra) and ILla were present in overlapping peaks. Further fractionation of the normal epidermal cytosol by anion exchange chromatography separated thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
66
0
2

Year Published

1992
1992
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 65 publications
8
66
0
2
Order By: Relevance
“…calcium concentration in the medium, in subconfluent cultures of the HaCAT spontaneously transformed keratinocyte cell line, the icIL-1 Ra: IL-1 a ratio does not rise above 16. By contrast, confluent cultures of HaCAT cells produce less IL-la and have a higher iclL-lRa:IL-la ratio (248: 1), which is of a similar order of magnitude to that reported for normal skin in vivo [9]. Diflerentiating keratinocytes, as found in confluent cultures, have previously been reported to contain higher IL-IRa levels, and non-differentiated keratinocytes higher IL-ln levels [6].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…calcium concentration in the medium, in subconfluent cultures of the HaCAT spontaneously transformed keratinocyte cell line, the icIL-1 Ra: IL-1 a ratio does not rise above 16. By contrast, confluent cultures of HaCAT cells produce less IL-la and have a higher iclL-lRa:IL-la ratio (248: 1), which is of a similar order of magnitude to that reported for normal skin in vivo [9]. Diflerentiating keratinocytes, as found in confluent cultures, have previously been reported to contain higher IL-IRa levels, and non-differentiated keratinocytes higher IL-ln levels [6].…”
Section: Discussionsupporting
confidence: 65%
“…The importance of assessing the IL-IRa ; IL-la ratio, rather than just the levels of the individual cytokines in isolation, is illustrated by recent studies on psoriasis. We and others [8,9] have documented reduced levels of ILIRa in lesional as opposed to involved skin from psoriasis patients. However, despite the reduction in keratinocyte IL-IRa inpsoriaticplaques.it has been reported that the IL-iRa: IL-la ratio in keratome skin biopsies is actually increased from 120:1 in normal skin to 1076:1 in psoriatic plaques, due to a diminution of IL-lrv levels [9].…”
Section: Introductionmentioning
confidence: 56%
“…The results of the present study show that it is unlikely that the decrease in IL-1 lev els is due to binding of IL-1 to an IL-l inhibitor [34], be cause the IL-1-inhibitor complex should have been detectĂ«d in the RIA by the polyclonal antibody, which rec ognizes different epitopes on IL -la [20] and such a com plex should be TCA-precipitable. It is also unlikely that the decrease in IL-1 activity is caused by an increase in IL-1 receptor antagonist [35][36][37], since the reduction in the IL-1 bioactivity paralleled a decrease in IL-1 im munoreactivity. Furthermore, we can exclude the involve ment of extracellular degradation of IL-1 by proteolytic enzymes, since 125I-IL-1 was not degraded when incu bated in the presence of supernatants derived from IL -1 -stimulated fibroblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…1-3), antagonist ligands [IL-1 receptor antagonist (IL-1ra); refs. [4][5][6], and both type 1 and type 2 IL-1 receptors (IL-1R1 and IL-1R2; refs. [7][8][9][10].…”
mentioning
confidence: 99%
“…This family of molecules binds to IL-1R1, but receptor occupancy by IL-1ra does not result in signal transduction (18). Thus, blockade of the IL-1R1 is an important means of limiting IL-1 activity (10,16,19), and under many circumstances, IL-1 gene expression appears to be paralleled by expression of the IL-1ra gene (5). The principal form of IL-1ra in keratinocytes is the intracellular IL-1ra, and it coexists in a cytoplasmic compartment with active preformed IL-1␣ in normal human and murine epidermis (6).…”
mentioning
confidence: 99%